Single chain peptide agonists of relaxin receptors. (1st May 2019) - Praveen, Praveen; Kocan, Martina; Valkovic, Adam; Bathgate, Ross; Hossain, Mohammed Akhter
Abstract: There are seven human relaxin family peptides that have two chains (A and B) and three disulfide bonds. The target receptors for four of these peptides are known as relaxin family peptide receptors, RXFP1-RXFP4. Detailed structure-activity relationship (SAR) studies of relaxin family peptides have been reported over the years and have led to the design of new analogs with agonistic and antagonistic properties. This review briefly summarizes the SAR of human relaxin 2 (H2 relaxin) and human relaxin 3 (H3 relaxin) leading to the design and development of single-B-chain only agonists, B7-33 and peptide 5. The physiological functions of these new peptides agonists in cellular and animal models are also described. Highlights: Human relaxin family peptides that have two chains (A and B) and three disulfide bonds target the GPCRs, RXFPs for biological functions. Single-B-chain only agonists of RXFP1 (B7-33) and RXFP3 (Peptide 5) have been designed and developed. The physiological functions of these new RXFP agonists in cellular and animal models are described.